Confocal total reflection X-ray fluorescence technology based on an elliptical monocapillary and a parallel polycapillary X-ray optics. (July 2018) - Zhu, Yu; Wang, Yabing; Sun, Tianxi; Sun, Xuepeng; Zhang, Xiaoyun; Liu, Zhiguo; Li, Yufei; Zhang, Fengshou
Abstract: A total reflection X-ray fluorescence (TXRF) spectrometer based on an elliptical monocapillary X-ray lens (MXRL) and a parallel polycapillary X-ray lens (PPXRL) was designed. This TXRF instrument has micro focal spot, low divergence and high intensity of incident X-ray beam. The diameter of the focal spot of MXRL was 16.5 µm, and the divergence of the incident X-ray beam was 3.4 mrad. We applied this TXRF instrument to the micro analysis of a single-layer film containing Ni deposited on a Si substrate by metal vapor vacuum arc ion source. Highlights: This is the first time that a MXRL was used in the TXRF without using slit. The divergence of the X-ray beam emitted from the MXRL is sufficiently low to meet the requirements of the TXRL. Due to the micro focal spot of the incident X-ray beam and confocal technology, this new TXRF instrument will be widely used in the field of microscopic analysis, which will help improve the processing technology.